Hydrogen Saturation Limit of Ti-Doped BN Nanotube With B-N Defects: An Insight From DFT Calculations - Mananghaya, Michael Rivera (Archīum Ateneo, 2018)
Ti-decorated (10,0) single-walled BN nanotubes (BNNTs) with B-N defects was fully examined by density functional theory (DFT). According to DFT formalisms, the HOMO-LUMO gap found for the Ti-BNNTs is small compared to that of a wide-gap semiconducting pristine BNNT. The Ti atom does not form any clusters and protrudes to the external surface of the sidewall. The calculations suggest that the Ti-BNNT assembly can attract small molecules and it has a good affinity towards H2 molecules. Up to seven H2 can partially attach to the system in quasi-molecular fashion due to the partially cationic character of the functionalized Ti and heteropolar bonds exhibited at the BNNT surface. The binding energies of H2 with Ti-BNNTs are within the optimal range for H2 storage. The unique electronic structure is barely perturbed upon adsorption and the (H2)7xTixBNNT systems hydrogen storage capacity is in compliance to the specifications mandated by the Department of Energy.